Improved Electrochemical Detection of Zinc Ions Using Electrode Modified with Electrochemically Reduced Graphene Oxide - Kudr, Jiri; Richtera, Lukas; Nejdl, Lukas; Xhaxhiu, Kledi; Vitek, Petr; Rutkay-Nedecky, Branislav; Hynek, David; Kopel, Pavel; Adam, Vojtech; Kizek, Rene (Materials (Basel, Switzerland), 2016)
Increasing urbanization and industrialization lead to the release of metals into the biosphere, which has become a serious issue for public health. In this paper, the direct electrochemical reduction of zinc ions is studied using electrochemically reduced graphene oxide (ERGO) modified glassy carbon electrode (GCE). The graphene oxide (GO) was fabricated using modified Hummers method and was electrochemically reduced on the surface of GCE by performing cyclic voltammograms from 0 to -1.5 V. The modification was optimized and properties of electrodes were determined using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The determination of Zn(II) was performed using differential pulse voltammetry technique, platinum wire as a counter electrode, and Ag/AgCl/3 M KCl reference electrode. Compared to the bare GCE the modified GCE/ERGO shows three times better electrocatalytic activity towards zinc ions, with an increase of reduction current along with a negative shift of reduction potential. Using GCE/ERGO detection limit 5 ng·mL-1 was obtained.
Keywords: graphene oxide; cyclic voltammetry; carbon; reduced graphene oxide; electrochemistry; electrochemical impedance spectroscopy; heavy metal detection